Electrical characterization of inorganic-on-organic diode based InP and poly(3,4-ethylenedioxithiophene)/poly(styrenesulfonate) (PEDOT:PSS) - Aydin, M. Enver; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2012)
The electronic properties of metal-organic semiconductor-inorganic semiconductor diode between InP and poly(3,4-ethylenedioxithiophene)/poly(styrenesulfonate) (PEDOT:PSS) polymeric organic semiconductor film have been investigated via current-voltage and capacitance-voltage methods. The Al/PEDOT:PSS/p-InP contact exhibits a rectification behavior with the barrier height value of 0.98 eV and with the ideality factor value of 2.6 obtained from their forward bias current voltage (I-V) characteristics at the room temperature greater than the conventional Al/p-InP (0.83 eV, n = 1.13). This increase in barrier height and ideality factor can be attributed to PEDOT:PSS film formed at Al/p-InP interface. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Capacitance-Voltage Characteristics; Interface State Density; Barrier Height; Semiconductor Contact; Temperature-Dependence; Current-Transport; Schottky Diodes; P-Type; Si; Junction